2019
DOI: 10.1002/gepi.22242
|View full text |Cite
|
Sign up to set email alerts
|

Genetic overlap between autoimmune diseases and non‐Hodgkin lymphoma subtypes

Abstract: Epidemiologic studies show an increased risk of non‐Hodgkin lymphoma (NHL) in patients with autoimmune disease (AD), due to a combination of shared environmental factors and/or genetic factors, or a causative cascade: chronic inflammation/antigen‐stimulation in one disease leads to another. Here we assess shared genetic risk in genome‐wide‐association‐studies (GWAS). Secondary analysis of GWAS of NHL subtypes (chronic lymphocytic leukemia, diffuse large B‐cell lymphoma, follicular lymphoma, and marginal zone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…Similarly, Ikeura et al [65] reported three cases (4.8%) of PC development during an average of 95 months of follow up in 63 AIP patients, whereas Ishida et al [66] reported the development of malignant lymphoma in the parotid gland seven months after the diagnosis of AIP. Even after successful discrimination of AIP from malignancies, clinicians must remain aware of the possible development of cancers [65,67,68] or lymphomas [68][69][70][71] during the follow up of the patients with AIP or IgG4-related diseases, as epidemiological [64,65,[67][68][69][70] or genetic [71] risks have been reported.…”
Section: Development Of Malignancies In the Course Of Aipmentioning
confidence: 99%
“…Similarly, Ikeura et al [65] reported three cases (4.8%) of PC development during an average of 95 months of follow up in 63 AIP patients, whereas Ishida et al [66] reported the development of malignant lymphoma in the parotid gland seven months after the diagnosis of AIP. Even after successful discrimination of AIP from malignancies, clinicians must remain aware of the possible development of cancers [65,67,68] or lymphomas [68][69][70][71] during the follow up of the patients with AIP or IgG4-related diseases, as epidemiological [64,65,[67][68][69][70] or genetic [71] risks have been reported.…”
Section: Development Of Malignancies In the Course Of Aipmentioning
confidence: 99%
“…Furthermore, there have been vast population studies to associate the presence of different etiologies, such as smoking, height, weight, autoimmune conditions, alcohol consumption, viral infections, and genetics, with the risk of developing any subtype of NHL [ 3 , 9 , 10 ]. Nevertheless, despite these efforts, there are only few established risk factors including autoimmune conditions (e.g., Sjögren disease, rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis), immunodeficiency syndromes, organ transplants, breast implants and specific infections (e.g., Helicobacter pylori for mucosa-associated lymphoid tissue lymphoma of the stomach, immunodeficiency virus, and mononucleosis) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a mutual relationship between connective tissue diseases and HMs. On the one hand, patients with a long-term history of connective tissue diseases including lupus erythematosus (LE), Sjogren's syndrome and systemic sclerosis demonstrate an increased risk of HMs, with special regard to B-cell lymphoma [203][204][205][206]. In patients with systemic LE, the closest association is with diffuse large B-cell lymphoma [207].…”
Section: Connective Tissue Diseasesmentioning
confidence: 99%
“…On the other hand, marginal zone lymphomas and those associated with mucosal-associated lymphoid-tissue lymphomas are the predominant subtypes observed in patients with Sjogren’s syndrome, where the incidence is up to 44-fold higher than the general population [ 208 , 209 ]. The pathogenesis of B-cell neoplasms in patients with connective tissue diseases is likely multifactorial, including some shared genetic/environmental factors, chronic inflammation, long-term immunosuppression and persistent high levels of cytokines such as IL-6, BAFF, APRIL and Blc2, which are involved in both autoimmune disease and lymphomagenesis, and, for systemic LE, Epstein–Barr virus infection [ 204 , 207 ].…”
Section: Miscellaneousmentioning
confidence: 99%